Implementasi Virtual Reality dalam Kegiatan Pembelajaran di Sekolah Dasar - Amdika Styadi; Lucia Sri Istiyowti (Lembaga Pengembangan Kinerja Dosen, 2025)
Many students find traditional learning methods to be uninteresting, which can lead to a lackluster classroom environment. This is often due to teachers delivering material that fails to engage students and a lack of interaction between teachers and students. As a result, students may struggle to understand the material presented to them, leading to suboptimal learning outcomes. However, advancements in technology offer solutions to this issue. The use of Virtual Reality (VR) is an effective way to support learning and make it more engaging. Studies show that incorporating VR in elementary school mathematics education can be particularly helpful. VR allows for a more realistic and contextual learning experience, making topics that are often considered difficult or boring more interesting and interactive. In addition, research has shown that technology such as Wolfram's Mathematica can improve students' understanding of mathematical concepts and computational skills. This research aims to explore teachers' understanding of the potential of VR as a learning medium and how it can be used to visualize abstract concepts that are challenging to grasp. By implementing this technology, we can improve learning outcomes for elementary school students.